2005
DOI: 10.1073/pnas.0509323102
|View full text |Cite
|
Sign up to set email alerts
|

Unexceptional sharpness of frequency tuning in the human cochlea

Abstract: The responses to sound of auditory-nerve fibers are well known in many animals but are topics of conjecture for humans. Some investigators have claimed that the auditory-nerve fibers of humans are more sharply tuned than are those of various experimental animals. Here we invalidate such claims. First, we show that forward-masking psychophysical tuning curves, which were used as the principal support for those claims, greatly overestimate the sharpness of cochlear tuning in experimental animals and, hence, also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
73
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 69 publications
3
73
2
Order By: Relevance
“…The results obtained from the mechanical model support Ruggero et al's findings of unexceptional human cochlear tuning sharpness at low frequencies, 10 and corroborate Shera et al's work on SFOAE, giving exceptionally sharp frequency tuning of the human cochlea at high frequencies. 7,11 The findings from all three approaches provide useful conclusions on the relative FTS of the human cochlea in different frequency regions.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…The results obtained from the mechanical model support Ruggero et al's findings of unexceptional human cochlear tuning sharpness at low frequencies, 10 and corroborate Shera et al's work on SFOAE, giving exceptionally sharp frequency tuning of the human cochlea at high frequencies. 7,11 The findings from all three approaches provide useful conclusions on the relative FTS of the human cochlea in different frequency regions.…”
supporting
confidence: 80%
“…11 Ruggero et al concluded that the human cochlear tuning sharpness is similar to those of these mammals and to that of squirrels, monkeys and cats. 10 However, Shera et al's results revealed sharper cochlear frequency tuning in humans 7,11 and macaque monkeys 12 compared with cats, guinea pigs and chinchillas, which is inconsistent with the work by Ruggero et al 10 Both Ruggero et al and Shera et al measured the ANF responses indirectly using unknown transformation functions. These attempts at defining a species-invariant rapidly varying function to describe the transform between the CAP-and the SFOAE-ANF Q-value require several species to provide reliable data.…”
contrasting
confidence: 53%
See 2 more Smart Citations
“…The sharpness of cochlear frequency tuning in humans is debated. Evoked otoacoustic emissions and psychophysical measurements suggest sharper tuning in humans than in laboratory animals [15], but this is disputed based on comparisons of behavioral and electrophysiological measurements across species [14]. Here we used evoked mass potentials to electrophysiologically quantify tuning (Q 10 ) in humans.…”
mentioning
confidence: 99%